2019
DOI: 10.1002/tox.22891
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA‐149‐5p/MyD88 axis is responsible for ursolic acid‐mediated attenuation of the stemness and chemoresistance of non‐small cell lung cancer cells

Abstract: Although the inhibitory roles of ursolic acid (UA) have been established in various tumors, its effects on the stemness of non‐small cell lung cancer (NSCLC) cells are still unclear. Here, we constructed NSCLC cells with paclitaxel resistance (A549‐PR) and showed that A549‐PR exhibited a remarkably stronger stemness than the parental A549 cells, which is evident by the increase of spheroid formation capacity, stemness marker expression, and ALDH1 activity. Additionally, UA significantly reduced the stemness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…However, the results showed that the overexpression of MDR1 could partially, but not completely, eliminate the regulatory effects of UA on Adriamycin resistance, which indicates that there are other molecular mechanisms and targets involved in UA‐mediated regulation on Adriamycin resistance. For example, the recent work indicates that UA attenuates paclitaxel resistance in non‐small cell lung cancer cells through inhibiting the miR‐149‐5p/MyD88 signaling 25 ; Consistently, UA reverses the paclitaxel resistance of breast cancer cells by targeting miR‐149‐5p/MyD88 26 ; And UA enhances the sensitivity of oxaliplatin in colorectal cancer by regulating reactive oxygen species production 9,27 . These results suggest that UA might regulate drug resistance through different mechanisms in different tumors.…”
Section: Discussionmentioning
confidence: 91%
“…However, the results showed that the overexpression of MDR1 could partially, but not completely, eliminate the regulatory effects of UA on Adriamycin resistance, which indicates that there are other molecular mechanisms and targets involved in UA‐mediated regulation on Adriamycin resistance. For example, the recent work indicates that UA attenuates paclitaxel resistance in non‐small cell lung cancer cells through inhibiting the miR‐149‐5p/MyD88 signaling 25 ; Consistently, UA reverses the paclitaxel resistance of breast cancer cells by targeting miR‐149‐5p/MyD88 26 ; And UA enhances the sensitivity of oxaliplatin in colorectal cancer by regulating reactive oxygen species production 9,27 . These results suggest that UA might regulate drug resistance through different mechanisms in different tumors.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, ursolic acid (UA) inhibited the phosphorylation of the AKT/BAD signaling pathway in drug‐resistant OSCC cells, which in turn activated intrinsic apoptotic mechanisms [ 176 ]. Additionally, UA attenuated cancer cell stemness and thus reversed chemoresistance by interfering with miR‐149‐5p [ 177 ]. As such, drugs targeting ncRNAs hold potential in alleviating the drug resistance of OSCC.…”
Section: Ncrna‐centered Approaches To Mitigate Drug‐resistance Of Osccmentioning
confidence: 99%
“…Myeloid differentiation primary response 88 (MyD88) is responsible for cell survival, DNA repair, and maintenance of stemness, thereby contributing to therapeutic resistance in cancer [ 275 , 276 ]. It was disclosed that ursolic acid reverses paclitaxel resistance by downregulating MyD88 levels in lung and breast cancer [ 85 , 146 ]. These studies also confirmed that miR-149-5p is upregulated in ursolic acid-treated cells and negatively affects MyD88 levels ( Figure 3 and Table 4 ).…”
Section: Tumor-suppressive Mirnas Induced By Phytochemicals Currenmentioning
confidence: 99%